2016
DOI: 10.1155/2016/4036232
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and Obesity: Possible Roles of Adipokines

Abstract: Multiple Sclerosis (MS) is an autoimmune disorder of the Central Nervous System that has been associated with several environmental factors, such as diet and obesity. The possible link between MS and obesity has become more interesting in recent years since the discovery of the remarkable properties of adipose tissue. Once MS is initiated, obesity can contribute to increased disease severity by negatively influencing disease progress and treatment response, but, also, obesity in early life is highly relevant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 266 publications
(257 reference statements)
0
68
0
1
Order By: Relevance
“…Interestingly, the present result indicated that BF% was significantly related to 1/AQP4 titer in NMOSD patients at acute phase. The role of adipose tissue in the pathogenesis of MS has become subject of great interest (Guerrero‐García et al, ). It is believed that increased fat mass, as well as the elevated levels of adipokines, may be involved in the altered immune response and inflammatory processes in NMOSD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the present result indicated that BF% was significantly related to 1/AQP4 titer in NMOSD patients at acute phase. The role of adipose tissue in the pathogenesis of MS has become subject of great interest (Guerrero‐García et al, ). It is believed that increased fat mass, as well as the elevated levels of adipokines, may be involved in the altered immune response and inflammatory processes in NMOSD.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, particularly during adolescence, has emerged as a risk factor for developing MS (61), and obese MS patients experience higher rates of comorbidities and greater disability (62). This is believed to stem from the pro-inflammatory effects of adipokines released from adipose tissue (63). Central obesity, as defined by increased waist circumference, is often indicative of metabolic syndrome, and is suggested to be a more potent risk factor than body mass index alone (64).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…ADIPOQ has anti-inflammatory activities in the immune system cells, and its low serum level is associated with disease severity [59]. ADIPOQ has anti-inflammatory activities in the immune system cells, and its low serum level is associated with disease severity [59].…”
Section: Discussionmentioning
confidence: 99%
“…ADIPOQ secreted by adipocytes functions through ADIPOQ receptor 1 (AdipoR1), which mediates the stimulation of AMPK phosphorylation and AdipoR2 which mediates PPAR-a activity [57]. PPAR-g signalling is also related to ADIPOQ, and its agonists can control EAE by preventing IL-1b, IL-6, nitric oxide (NO) and TNF-a production (by astrocytes and microglia) and inhibiting T helper type 1 (Th1) differentiation and IL-12 generation/signalling [59]. production, and enhancement of regulatory T cell count and IL-10 secretion [57,58].…”
Section: Significant Protein Complexes and Ms-related Genes In The Ndmentioning
confidence: 99%
See 1 more Smart Citation